STUDENT BEHAVIOR ANALYSIS AND SELF-INJURY HANDLING (CASE STUDY AT SMPN 8 MAKASSAR) - Ulum, Nur Nahdatul; Harum, Akhmad; Zulfikri, Zulfikri (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study explores self-injury behavior among students at SMPN 8 Makassar by focusing on: (1) the description of self-injury behavior exhibited by subject H, (2) factors contributing to the behavior, and (3) intervention efforts using a Cognitive Behavioral Therapy (CBT) approach. A qualitative method with a clinical case study design was employed. Data were collected through interviews, observations, and documentation, and analyzed using descriptive qualitative analysis. The findings show that prior to counseling, subject H displayed repetitive self-injury as a maladaptive response to unexpressed emotional distress, primarily related to family conflict, feelings of failure, and persistent negative thoughts. Following the counseling intervention, there was a noticeable reduction in the frequency and intensity of self-injury behavior, decreased urges during negative emotional states, and improved ability to express emotions verbally. Contributing factors included internal aspects such as cognitive distortions, irrational beliefs, and negative thinking patterns, as well as external factors like limited emotional support from the family and an unstable home environment. The intervention was conducted through seven CBT counseling sessions emphasizing cognitive restructuring, including identifying automatic thoughts, challenging irrational beliefs, developing adaptive coping thoughts, and establishing a safety plan. Overall, the intervention contributed to more rational thinking, better emotional regulation, and reduced maladaptive coping behaviors.